1997
DOI: 10.1177/0310057x9702500608
|View full text |Cite
|
Sign up to set email alerts
|

Do Intensive Care Drug Infusions Support Microbial Growth?

Abstract: The potential for commonly infused drug solutions to support or inhibit microbial growth was explored in this study. Drugs examined were midazolam HCl, morphine sulphate, fentanyl citrate, pethidine HCl, bupivacaine HCl, atracurium besylate, vecuronium bromide, adrenaline, dopamine, dobutamine, noradrenaline, isoprenaline, glyceryl trinitrate, sodium nitroprusside and propofol. All drugs were studied in both diluted and undiluted forms. Of the 15 medications investigated, all except propofol were found to be b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…[12][13][14][15][16] PE has been associated with pain-oninjection, 17,18 elevated lipid levels during long-term infusions, [19][20][21][22] and risk of infection due to bacterial contamination. [23][24][25] Propofol is also associated with dose-dependent apnea and hemodynamic depression. 1,26 Following i.v.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] PE has been associated with pain-oninjection, 17,18 elevated lipid levels during long-term infusions, [19][20][21][22] and risk of infection due to bacterial contamination. [23][24][25] Propofol is also associated with dose-dependent apnea and hemodynamic depression. 1,26 Following i.v.…”
Section: Introductionmentioning
confidence: 99%
“…coli (ATCC 25922) or P. aeruginosa (ATCC 27853) was not affected by pH 5.0 to 8.0 17 . In some studies the pH range of midazolam was thought to be responsible for the inhibitor effect 18,19 . On the other hand, in another study it is concluded that the antimicrobial effect of midazolam was due to the fact that it included HCl as a preservative 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Dagegen konnte die Arbeitsgruppe um Vidovich überhaupt keinen Effekt von Lidocain auf das Keimwachstum in Propofol nachweisen [122]. EDTA ist in einer Konzentration von 0,005 Gew-% in der Lage, die Vermehrung von Keimen sehr wirksam zu verhindern [14,39].Seit 1996 ist in den USA deshalb nur noch die Verwendung von Propofol mit diesem EDTA-Zusatz gestattet.Danach sind dort keine weiteren Infektionsfälle mehr bekannt geworden.…”
Section: Infektionsrisiko Durch Kontaminiertes Propofol Edta-zusatzunclassified